2017
DOI: 10.1557/mrc.2017.105
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of mechanically exfoliated MoS2 flakes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 23 publications
2
43
3
Order By: Relevance
“…Having established the likely edge morphology, we can investigate ambient stability of 2H‐TaS 2 nanoparticles by calculating their susceptibility to oxidation. The oxidation is assumed to initiate at the edge, in accordance with recent experimental and theoretical evidence [37,42,43,53–55] . Here, we consider both the one dimensional nanostripe as well as the triangular cluster.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Having established the likely edge morphology, we can investigate ambient stability of 2H‐TaS 2 nanoparticles by calculating their susceptibility to oxidation. The oxidation is assumed to initiate at the edge, in accordance with recent experimental and theoretical evidence [37,42,43,53–55] . Here, we consider both the one dimensional nanostripe as well as the triangular cluster.…”
Section: Resultsmentioning
confidence: 89%
“…The oxidation is assumed to initiate at the edge, in accordance with recent experimental and theoretical evidence. [37,42,43,[53][54][55] Here, we consider both the one dimensional nanostripe as well as the triangular cluster. For both models, we consider oxidation of the Ta-edge covered by 50 % sulfur atoms, which is found to be the most stable edge in previous section.…”
Section: Oxidation Of 2h-tasmentioning
confidence: 99%
“…The photo-oxidation of semiconductors is not limited to direct bandgap materials, and has also been reported for silicon (note that CrI3 also has an indirect bandgap), 54 although the effect was found to be less pronounced than for direct bandgap materials. 46 Thus, it is expected that even multilayers of S-TMDs will undergo ambient air photo-oxidation, and indeed this has been reported by Budania et al 52 which observed oxidation in exfoliated multilayer MoS2 samples left in ambient conditions (though the role of light was not investigated). The photoinduced oxidation of semiconductors in ambient atmosphere seems to be a universal effect, yet not much attention has been paid to the mechanism in the 2D community, especially in regard to S-TMDs.…”
Section: Discussionmentioning
confidence: 89%
“…The environmental stability is another important property of 2D materials. For many 2D materials, such as BP [19,21,[96][97][98] and TMDCs [99][100][101][102], instability has severely hindered their further development in both academic and industrial applications. In sharp contrast, extraordinary environmental stability has been demonstrated for various thicknesses of 2D Te (ranging from few-layer to monolayer).…”
Section: Stabilitymentioning
confidence: 99%